Russian and Slovenian: Linguistic deviations in Russian under the influence of Slovenian as a dominant language - Makarova Tominec, Irina (Jezikoslovni zapiski, 2018)
This article describes the status of Russian-speaking immigrants in Slovenia, presents the findings of a sociolinguistic study of primarily younger members of the Russian emigre community, and analyzes the common changes that occur in the language of especially second-generation Russian-speaking residents of Slovenia under the influence of Slovenian as the dominant language. It presents a systematized description of common deviations from the Russian linguistic standard established in both the written and oral communication of Russian-Slovenian bilinguals. Based on the data collected through the analysis of secondary-school exit exam essays, personal interviews, and an online survey, the major factors influencing the development of Russian communicative competence in bilingual children are established.